2014
DOI: 10.1055/s-0033-1363253
|View full text |Cite
|
Sign up to set email alerts
|

Injury Risk Due to Collisions in Major League Baseball

Abstract: Purpose is to determine if Major League Baseball plays at risk for collisions have higher injury rates than typical base running plays. 2002-2011 Major League Baseball play data was obtained: non-force putouts by catcher at home plate (Catcher Tag Out), groundball force outs at 2(nd) base with less than 2 outs (Double Play Attempt), and the control play, outfield assisted non-force putouts of runners attempting to advance to 2(nd) or 3(rd) base (Outfield Assist 2(nd)/3(rd)). This list was cross-referenced with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…One study has shown that home plate outs are more likely to result in injury than similar plays at second and third bases. 15 It has been suggested that the reason catchers experience a higher percentage of concussions is that they have a higher overall injury rate compared with other positions. An ad hoc exploration of our data revealed that this is not the case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study has shown that home plate outs are more likely to result in injury than similar plays at second and third bases. 15 It has been suggested that the reason catchers experience a higher percentage of concussions is that they have a higher overall injury rate compared with other positions. An ad hoc exploration of our data revealed that this is not the case.…”
Section: Discussionmentioning
confidence: 99%
“…One study has shown that home plate outs are more likely to result in injury than similar plays at second and third bases. 15…”
Section: Discussionmentioning
confidence: 99%
“…The 3 sports included in the NCC group were chosen with the intention of including contact sports that, on average, range from a low to high degree of contact based on previous studies. 15 , 16 , 17 , 18 , 19 The inclusion of baseball serves the NCC group as a contact sport with a low degree and frequency of contact 15 , 19 , 20 , 21 ; basketball serves as a contact sport with an intermediate degree of contact 15 , 19 ; soccer serves as a contact sport with a high degree and frequency of contact, but wherein collision between players is prohibited. 16 , 17 Notably, all the sports included in the sample are team-based sports with a high frequency of injuries due to falls or incidental contact with other players and/or the sporting equipment (balls, pucks, sticks, etc.).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, using only players who had an injury severity that warranted placement on the DL does not capture all injuries and is subject to nonmedical factors that are weighed into the decision to place a player onto the DL. 1-3,5,7 Nonetheless, information obtained from evaluating MLB’s DL can play a role in injury prevention. For example, in 2016, MLB and the MLB Players Association adopted a rule modification to reduce the number of intentional collisions while sliding into second base to break up a double play.…”
Section: Introductionmentioning
confidence: 99%